Balanced Anaesthetic Approach in a Late-Term Gravid Cow Undergoing Metacarpal Fracture Repair. (15th December 2011) - Martin Jurado, Olga; Jud, Rahel; Muggli, Evelyne; Bettschart-Wolfensberger, Regula
Abstract : An 800 kg Swiss cow, eighth months gravid, was presented for anaesthesia to repair metacarpal fracture. The cow was premedicated with intravenous isoxsuprine, butorphanol, ketoprofen, and xylazine IM and induced with ketamine and diazepam IV. In lateral recumbency, the trachea was intubated, and isoflurane in oxygen and air was administered. Despite a ring block with lidocaine, purposeful movement happened, and xylazine 0.02 mg kg −1  h −1 and ketamine 0.6 mg kg −1  h −1 constant rate infusion was started. During anaesthesia, slight hypercapnia and hypoxaemia developed. Total time of xylazine and ketamine infusion was 3.5 hours. Total anaesthesia time was 4.5 hours. For recovery of anaesthesia, isoflurane was discontinued, and in sternal recumbency, the trachea was extubated when the cow swallowed. Paralysis of the left radial nerve occurred, and the cow was supported to stand up after 2 hours. The radial nerve paralysis resolved within three days. A healthy calf was born at term. This is the first paper that describes the successful use of adjunctive xylazine and ketamine infusion to isoflurane anaesthesia in a late-term gravid cow undergoing fracture repair during 4.5 hours.